Effect of Electronic Word of Mounth (E-WOM), Product Quality and Price Perception of Repurchase Intention of Skincare Products on the Tiktok Shop Application - Fakhirah; Hadi, Effed Darta (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to determine the influence of Electronic Word of Mount (E-Wom), Product Quality and Price Perception on Repurchase Intention for Skincare Products on the Tiktok Shop Application. Descriptive qualitative with survey design is the type of research used. This research is a type of quantitative research that uses data collection techniques in the form of questionnaires or surveys whose results are analyzed statistically using the SPSS 23 data analysis model. The sample in this research was 160 with respondents in the category of having purchased skincare products on the Tiktok Shop application. The research results show that E-WOM has an insignificant influence on repurchase intention on skincare products in the Tiktok application, while product quality has a significant influence on repurchase intention on skincare products in the Tiktok Shop application and price perception has a significant influence on repurchase intention on skincare products in TikTok Shop application.